2013
DOI: 10.1002/pmh.1241
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated youth with personality disorders: Prevalence, comorbidity and convergent validity

Abstract: Results indicate that personality disorders can be found in incarcerated youth at high rates. These findings further our understanding of chronic psychiatric illness and possibly criminal recidivism in this at-risk population. Addition of personality measures in the assessment of delinquents may assist in the development of more effective interventions. Furthermore, the supportive convergent validity of these findings in a population younger than 18 years may indicate a need to reassess the current rationale f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…the interstitial nature of four facets; Krueger et al, 2012). In addition, obtaining such a perfect structure might be even more difficult in clinical studies (such as the current study), where maladaptive traits are typically more strongly connected, leading to higher cross-loadings and a less distinctive factor matrix (Kaszynski et al, 2014;Quilty et al, 2013;Verbeke, De Caluwé, & De Clercq, 2017). A second limitation concerns the exclusive use of self-reports, and despite the fact that this may be the best way to assess maladaptive traits, other informants (e.g., parents) could also provide extra information .…”
Section: Discussionmentioning
confidence: 92%
“…the interstitial nature of four facets; Krueger et al, 2012). In addition, obtaining such a perfect structure might be even more difficult in clinical studies (such as the current study), where maladaptive traits are typically more strongly connected, leading to higher cross-loadings and a less distinctive factor matrix (Kaszynski et al, 2014;Quilty et al, 2013;Verbeke, De Caluwé, & De Clercq, 2017). A second limitation concerns the exclusive use of self-reports, and despite the fact that this may be the best way to assess maladaptive traits, other informants (e.g., parents) could also provide extra information .…”
Section: Discussionmentioning
confidence: 92%
“…Antisocial personality disorder is also frequently found in male young offenders, with prevalence rates ranging from 76 to 81 % [4, 6]. A recent study [8] further shown that male young offenders with personality disorders have high levels of anger–irritability, aggression, delinquency, distress, and reduced restraint, when compared with young offenders without personality pathology. Other than conduct disorder and/or antisocial personality disorder, male young offenders still present considerably high rates of psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…In line with this theory, Heleniak and colleagues [ 21 ] found in youth of a community sample that emotional dysregulation mediated the relations between maltreatment and psychopathology. In juvenile detainees, irritability was associated, amongst others, with antisocial, borderline, and narcissistic personality disorders [ 22 ], and was found to predict violent criminal re-offenses after release from detention [ 23 ]. By taking into account these recent findings, the present study addresses the specific impact of cumulative ACEs while controlling for irritability symptoms.…”
Section: Introductionmentioning
confidence: 99%